ODL- our future direction of education?? / Li Sian Tey ... [et.al] - Li, Sian Tey; Melati, Shareena; Woei, Keong Kuan; Hooi, Ming Yee (Unit Penerbitan FKAPP, 2022)
Online Distance Learning (ODL) has been widely implemented in Malaysia since the first lockdown on the 18th March 2019 due to the COVID'19. In ODL, students have more choices in learning what they want without the limitation of time and space. Here, we conducted a simple survey to evaluate the students' preference on different options they were exposed to in ODL and conventional face to face lectures in our faculty.